Renal functional reserve is impaired in patients with systemic sclerosis without clinical signs of kidney involvement. Issue 8 (1st August 2002) - Livi, R; Teghini, L; Pignone, A; Generini, S; Matucci-Cerinic, M; Cagnoni, M
Abstract : Objective: To evaluate the functional response of the kidney to an amino acid challenge (the so called renal functional reserve (RFR)) in patients with systemic sclerosis (SSc) with no clinical sign of renal involvement. Methods: Before and after an intravenous amino acid load (Freamine III Baxter, 8.5% solution, 4.16 ml/min for two hours), glomerular filtration rate (GFR, as creatinine clearance), effective renal plasma flow (ERPF, as para-aminohyppurate clearance), and calculated total renal vascular resistance (TRVR) were measured in 21 patients with SSc with apparently normal renal function and 10 normal controls. Results: In basal conditions, patients had lower ERPF (403.5 (SD 43.8) v 496.4 (SD 71.3) ml/min, p<0.0002) and higher TRVR (10 822 (SD 2044) v 8874 (SD 1639) dyne/s×cm -5, p<0.014) than controls. The RFR, evaluated as the percentage increase of GFR after the amino acid load, was significantly reduced in patients with SSc (SSc +1.9 (SD18.6)%, controls +34.8 (SD 13.9)%; p<0.0002). However, the response of patients was not uniform. Multiple regression analysis showed that the RFR was inversely dependent on the patients' mean arterial pressure at admission and basal GFR ( R 2 =65%, p<0.0001). Conclusions: Most patients with SSc cannot increase renal filtration under the challenge of a protein overload. This defective renal response to the amino acid load test sustains the concept of the prevalence of vasoconstrictor over vasodilating factors in the kidney of these patients.